2015
DOI: 10.1002/adsc.201400659
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Cross Dehydrogenative Coupling of N,N‐Disubstituted Formamides and Phenols: A Direct Access to Carbamates

Abstract: An efficient copper‐catalyzed protocol has been developed for the synthesis of carbamates from dialkylformamides and phenols possessing directing groups such as benzothiazole, quinoline and formyl at the ortho‐position. In this chelation assisted approach, CO bond formation takes place via a cross dehydrogenative coupling (CDC) between the formyl CH of dialkylformamide and phenolic OH in the presence of copper(II)acetate/aqueous tert‐butyl hydroperoxide. Under identical reaction conditions, salicylic acid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 111 publications
0
37
0
Order By: Relevance
“…Carbamates are usually prepared by using phosgene or its substitutes. Synthesis of carbamtes by nobel metal catalyzed oxidative carbonylation of amines circumvent the use of toxic phosgene . Carbamates are also synthesized by using CO 2 .…”
Section: Coupling Chemistrymentioning
confidence: 99%
“…Carbamates are usually prepared by using phosgene or its substitutes. Synthesis of carbamtes by nobel metal catalyzed oxidative carbonylation of amines circumvent the use of toxic phosgene . Carbamates are also synthesized by using CO 2 .…”
Section: Coupling Chemistrymentioning
confidence: 99%
“…Patel et al reported coupling between formamides and phenols containing directing groups in their o ‐positions to furnish phenol carbamates in the presence of copper acetate/ tert ‐butyl hydroperoxide (Scheme ) . Directing groups such as benzothiazole and quinoline systems, in which the N atom activates the hydroxy group present at the adjacent carbon atom in the phenol component, were effective in facilitating the formation of the coupled product.…”
Section: Cdc Of Nn‐disubstituted Formamidesmentioning
confidence: 99%
“…The scope of the reaction has been extended to phenols containing formyl group at the ortho position (i.e., salicylaldehydes). The coupled products were obtained in reasonable yields (Scheme ) …”
Section: Cdc Of Nn‐disubstituted Formamidesmentioning
confidence: 99%
“…8,9 Previously, Ali and et al developed the rst illustration of a synthetic method to produce structures containing both carbamates and benzothiazoles via the Cu(OAC) 2 -catalyzed coupling reaction between dialkylformamides and phenols having benzothiazole directing substituents (Scheme 1a). 10 Zheng et al also synthesized phenol esters possessing cyano, azo, and pyridine moieties by using the Cu(OAC) 2 -catalyzed transformation between aldehydes and 2-substituted phenols.…”
Section: -3mentioning
confidence: 99%
“…Indeed, tert-butyl hydroperoxide was also the oxidant of choice in previous works. 10,11,30 Having these results, we also explored the inuence of oxidant concentration on the transformation (entries 25-29, Table 1). The reaction could not proceed without an oxidant, and no trace quantity of the expected product was detected aer 24 h (entry 25, Table 1).…”
mentioning
confidence: 99%